Política cultural exterior alemana en España durante la República de Weimar - López Sánchez, José María (Cuadernos de Historia Contemporánea, 2003)
The emergence of a scientific policy in Germany at the end of the 19th century and at the beginning of the 20th century is due to the fact that efficiency of the German scientific burocracy system. The Althoff’s System and the Notgemeinschaft der Deutschen Wissenschaft were the most significant outcomes of one policy which strove for placing Germany on the top of the European scientific development.